Structure−performance correlation guided applications of covalent organic frameworks - Wang, Hou (2022)
Pre-designed structures and tailor-made functions make covalent organic frameworks (COFs) quickly become promising reticular platforms for multidisciplinary fields. Despite the overarching success, controllable and large-scale synthesis of COFs is still a huge challenge. Moreover, the relationship between the structure and performance of COFs in various fields has not been well understood, seriously limiting their practical applications. In this review, we provide an insightful and fundamental understanding of COFs from structural perspectives, and correlate them with eventual performance in practical applications. By summarizing both the top-down and bottom-up approaches, we address how typical issues, such as the size, morphology, dispersity and stability of COFs, are resolved, which should be crucial for their function-oriented and large-scale production. Structural and physicochemical properties, such as pores, ligands, stacking, linkages, functional group, morphology, crystallinity, dimensionality and wetting, are also discussed in relation to various functions. In addition, in-depth discussions regarding the correlations between structural characteristics of COFs and their performance in catalysis, energy storage, gas/liquid adsorption and membrane separation are presented. Finally, perspectives for the future direction of this field are proposed, to provide useful guidance for the function-oriented design and scalable production of COFs to meet the practical requirements of applications.